Peran Guru Pendidikan Agama Islam dalam Menangani Perubahan Moral Peserta Didik Akibat Pengaruh Kemajuan Teknologi - Suriyati; Isnaeni; Nurqadriani; Mustamir (Al Asma: Journal of Islamic Education, 2023)
This article was compiled to examine and describe the role of Islamic religious education teachers in dealing with changes in student morale due to the influence of technological advances at SMK Negeri 1 Sinjai. This research is a qualitative research. The data collection method in this study is by summarizing the results of interviews, observation and documentation. The source of the data in this study was the PAI teacher at SMK Negeri 1 Sinjai, the data used were primary data and secondary data as well as the results of previous studies that were considered relevant. After the data is collected, content analysis is carried out to get precise and accurate conclusions. The focus in this study is moral change and technological progress. The results of this study indicate that changes in student morale due to technological advances at SMK Negeri 1 Sinjai experience changes in attitude/moral crisis. So that PAI teachers provide assistance, guidance and coaching by instilling religious values in students so that they have spiritual strength.